Systematic Literature Review: Trends in Maths Learning Media for Students with Learning Disabilities - Hasanah, Aan; Afifah, Aqilah Nur; Azzahra, Rahmi Nur'aini; Aulia, Septiani; Azwar, Shiva Anugrah; Mu'afi, Yusniar Najmah (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2024)
Mathematics is a discipline that studies logic, making it challenging to teach abstract and conceptual topics to students with intellectual disabilities. This study aims to systematically review educational research related to mathematics learning media for students with intellectual disabilities using a Systematic Literature Review (SLR) methodology. The research employed the PRISMA method using Covidence software. Initially, 200 articles indexed in Google Scholar were obtained through Publish or Perish using keywords such as "learning media," "mathematics learning," and "intellectual disabilities." After processing through Covidence, 38 articles meeting the researchers' criteria were selected. The analysis revealed that most articles were published in 2023, with a majority conducted in East Java. The article titled "Educational Counting Games for Elementary School Children Using Mobile-Based RPG Maker" was the most cited, with 265 citations. The most commonly used research method was Classroom Action Research (CAR). Additionally, the most frequently used learning media were teaching aids, mentioned in 12 articles.